-1(x-4)+2=6(x+3)

Simple and best practice solution for -1(x-4)+2=6(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1(x-4)+2=6(x+3) equation:


Simplifying
-1(x + -4) + 2 = 6(x + 3)

Reorder the terms:
-1(-4 + x) + 2 = 6(x + 3)
(-4 * -1 + x * -1) + 2 = 6(x + 3)
(4 + -1x) + 2 = 6(x + 3)

Reorder the terms:
4 + 2 + -1x = 6(x + 3)

Combine like terms: 4 + 2 = 6
6 + -1x = 6(x + 3)

Reorder the terms:
6 + -1x = 6(3 + x)
6 + -1x = (3 * 6 + x * 6)
6 + -1x = (18 + 6x)

Solving
6 + -1x = 18 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
6 + -1x + -6x = 18 + 6x + -6x

Combine like terms: -1x + -6x = -7x
6 + -7x = 18 + 6x + -6x

Combine like terms: 6x + -6x = 0
6 + -7x = 18 + 0
6 + -7x = 18

Add '-6' to each side of the equation.
6 + -6 + -7x = 18 + -6

Combine like terms: 6 + -6 = 0
0 + -7x = 18 + -6
-7x = 18 + -6

Combine like terms: 18 + -6 = 12
-7x = 12

Divide each side by '-7'.
x = -1.714285714

Simplifying
x = -1.714285714

See similar equations:

| 4x+11x=-2 | | 6+3x=-15-4x | | m-4-6m= | | 3(3k+6)-8= | | 2x-9+5+6x= | | 10y=3x | | 9x-9=8x-13 | | -8k-10k= | | 4x+3+5= | | 4x+7=-8x+7 | | 8v^3+18v^2-56v= | | 1.1y+1.4=8 | | 5x+7=7-2x | | 7(x-2)=3+7x | | -12-5n+n=n-2 | | 14-n-7=5n+1 | | 1-7k=1+3k+4k | | 8-9x+10x=5 | | 8b+6=-9+3b | | 32-6b-5b=7.25 | | 3+3x=x-3 | | 1+7r=-7+3r | | 2(5x-1)=3x(x+1) | | 8x-2=-7+7x | | 2x+8=-5 | | -107=3-10x | | 7n+3=-67 | | 7=6-v | | 5c-3-4c=2c+2 | | 160+(16x+32)=180 | | 3a=1 | | (3x-4)(x^2-5x+1)= |

Equations solver categories